Pengaruh Cost Of Loanable Fund, Overhead Cost, dan Risk Factor Terhadap Tingkat Margin Pembiayaan Berbasis Natural Certainty Contract di Industri Perbankan Syariah - Riris Rizky Hayati; Noven Suprayogi (Universitas Airlangga, 2015)
The purpose of this study is to find out which of the three component parts were cost of loanable funds, overhead costs and risk factors that have a significant effect in determining the margin rate of natural certainty contracts-based financing in Islamic banking industry. This study uses two natural certainty contracts financing agreement, which is murabaha and istisnaa. This study uses a quantitative approach. The statistical tool used is multiple regression time series. The sample used is the Islamic Banks and Sharia Business Unit which data summarized in statistical reports of Islamic banking. The research period is 2009-2013 years. The results of this study is all three rate component simultaneously affect margin rate of murabaha and margin rate of istisnaa. Partial test results were variable risk factors significantly affect the margin rate of murabaha, and variable overhead costs significantly affect the margin rate of istisnaa